Planktonic and periphytic bdelloid rotifers from Thailand reveal a species assemblage with a combination of cosmopolitan and tropical species. Issue 2 (17th February 2018) - Jaturapruek, Rapeepan; Fontaneto, Diego; Meksuwan, Phuripong; Pholpunthin, Pornsilp; Maiphae, Supiyanit
Abstract : The dispersal pattern of microorganisms has been a debated topic in the last decade, because for microscopic organisms with dispersing stages, biogeographic barriers may not exist and geographic distances may have little effect on the probability of their occurrence. In this study we tested whether a group of microscopic animals, the bdelloid rotifers, sampled in a tropical country, could indeed be cosmopolitan, strictly tropical, and/or have endemic species. We sampled freshwater habitats throughout Thailand in dry and rainy seasons between 2014 and 2016, focusing on permanent water bodies, where the prevalence of species producing resting stages acting as propagules for dispersal should be minimal and thus dispersal limitation should exist, with several species being narrowly distributed. We used traditional morphological identification, geometric morphometric analyses on the shape and size of the jaws, and DNA taxonomy to identify species and to quantify the morphological and genetic distances of Thai samples in comparison with data on bdelloids from other areas in the world. We found a total of 12 species of planktonic and periphytic bdelloid rotifers, and all approaches we used, qualitative and quantitative, confirmed a group of nine potentially cosmopolitan species already known from other continents, one tropical oriental species, and two new species with a potentially narrow geographic distribution, one of which we here formally describe. We thus support the idea that for microscopic animals the moderate endemicity hypothesis suggested for protists may also hold true: most of the species we found indeed have a wide geographic distribution, but other species with narrower distributions do exist. http://zoobank.org/urn:lsid:zoobank.org:pub:3DF5A913-BE6A-4EA4-88FD-C38C0F7AE00A